Influence of Roof Slope on Timber Consumption in Plane Trusses Design - Fraga, Iuri Fazolin; Morato de Moraes, Matheus Henrique; Menezes, Isabella Silva; Arroyo, Felipe Nascimento; Boff de Almeida, Joao Paulo; Castanheira Rodrigues, Edson Fernando; Mascarenhas, Fernando Resende; Moura Aquino, Vinicius Borges de; Mello Silva, Sergio Augusto [UNESP]; Rocco Lahr, Francisco Antonio; Pereira, Wanderlei Malaquias; Christoforo, Andre Luis (North Carolina State Univ Dept Wood & Paper Sci, 2021)
The growing world consumption of wood in civil construction is evident, especially in structural roofing systems. Despite being from a renewable source, its rational and intelligent use is of vital importance in the execution of structural designs. Because it is a system that is recognized worldwide in the design of trussing roof structures, there are several empirical assumptions for structural calculation. To reduce timber consumption, some tile manufacturers suggest a 10% (6 degrees) slope between chords. However, after simulations of 11 slopes with angles from 5 degrees to 15 degrees, the timber consumption was inversely proportional to the slope, reaching a 90% difference between extreme angles. The method used to obtain the results was software designed according to the routines prescribed by the new draft standard of ABNT NBR 7190 (2021). Considering a prefabricated truss with 5 cm thickness sections, the design criterion was that of minimum height, increasing by 0.10 cm until all checks were satisfied. Finally, the minimum angle after which no strengthening is required on the bars was 10 degrees.
Keywords: Timber structures; Plane trusses; Slope; Design; Timber consumption